Home blood pressure-lowering effect of esaxerenone versus trichlormethiazide for uncontrolled hypertension: a predefined subanalysis of the EXCITE-HT randomized controlled trial by basal calcium channel blocker versus angiotensin receptor blocker - Kario, Kazuomi; Ohbayashi, Hiroyuki; Hashimoto, Masami; Itabashi, Naoki; Kato, Mitsutoshi; Uchiyama, Kazuaki; Hirano, Kunio; Nakamura, Noriko; Miyamoto, Takahide; Nagashima, Hirotaka; Ishida, Hidenori; Ebe, Yusuke; et al. (Hypertension research, 2025)
This prespecified subanalysis of the multicenter, randomized, open-label, parallel-group EXCITE-HT study aimed to examine the non-inferiority of esaxerenone to trichlormethiazide as a second-line antihypertensive agent according to the basal antihypertensive agent used (angiotensin receptor blocker [ARB] or calcium channel blocker [CCB]). The primary endpoint, change in morning home systolic/diastolic blood pressure (SBP/DBP) from baseline to end of treatment was similar between the two groups (intergroup difference in least squares mean change [95% confidence interval]: −1.3 [−3.8, 1.3]/−0.2 [−1.6, 1.3] mmHg for ARB; −2.7 [−4.2, −1.2]/−0.8 [−1.7, 0.1] mmHg for CCB). The respective incidences of serum potassium levels <3.5 mEq/L and ≥5.5 mEq/L in the ARB subgroup were 3.4% and 4.2% for esaxerenone and 7.9% and 0% for trichlormethiazide; in the CCB subgroup, they were 2.8% and 0.6% for esaxerenone and 13.9% and 1.2% for trichlormethiazide, respectively. The incidence of uric acid level ≥7.0 mg/dL was numerically higher in the trichlormethiazide group than the esaxerenone group in both the ARB and CCB subgroups. The non-inferiority of esaxerenone to trichlormethiazide in lowering morning home BP was demonstrated regardless of whether the basal antihypertensive agent was an ARB or CCB. Esaxerenone with a CCB showed superiority to trichlormethiazide in lowering SBP, without any new safety concerns. Serum potassium levels tended to be higher when esaxerenone was combined with an ARB than with a CCB, but this can be mitigated if administered according to the package insert. A subgroup analysis of the EXCITE-HT study according to basal antihypertensive agent demonstrated the non-inferiority of esaxerenone to trichlormethiazide in lowering morning home BP regardless irrespective of the basal antihypertensive agent. Esaxerenone with a CCB showed superiority to trichlormethiazide in lowering SBP, without any new safety concerns. A subgroup analysis of the EXCITE-HT study according to basal antihypertensive agent demonstrated the non-inferiority of esaxerenone to trichlormethiazide in lowering morning home BP regardless irrespective of the basal antihypertensive agent. Esaxerenone with a CCB showed superiority to trichlormethiazide in lowering SBP, without any new safety concerns.